2013
DOI: 10.1080/19407963.2013.776371
|View full text |Cite
|
Sign up to set email alerts
|

Place attachment, place satisfaction and pro-environmental behaviour: a comparative assessment of multiple regression and structural equation modelling

Abstract: Using data collected from 452 visitors at the Dandenong Ranges National Park, Australia, this paper applies multiple regression and structural equation modelling (SEM) approaches to test the relationships between the respective sub-constructs of place attachment (place dependence, place identity, place affect, place social bonding), place satisfaction, and visitors' pro-environmental behavioural intentions. Findings revealed differences in strength and magnitude of the regression paths. The SEM analysis furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 75 publications
2
36
2
1
Order By: Relevance
“…This suggests that when the respondents' sense of place has increased, it is likely that there might be lower satisfaction with the landscaping they have. Although these results do not coincide with the findings of the studies by Stokols and Shumaker (1981), Smith (2011) and Ramkissoon et al (2013), however, this result is in accordance with the Stedman's work (2003) on the fact that without being strongly satisfied, people can still be attributed to the place in which they live. This again suggests that when residents have developed strong bonding with their living place, their judgements might be offering detail and focused on the inadequacies and weaknesses in the landscaping with a demand for living in a better environment and also with a comparison of the ideal or reference landscaping along with the intention to continue living in their current living place.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…This suggests that when the respondents' sense of place has increased, it is likely that there might be lower satisfaction with the landscaping they have. Although these results do not coincide with the findings of the studies by Stokols and Shumaker (1981), Smith (2011) and Ramkissoon et al (2013), however, this result is in accordance with the Stedman's work (2003) on the fact that without being strongly satisfied, people can still be attributed to the place in which they live. This again suggests that when residents have developed strong bonding with their living place, their judgements might be offering detail and focused on the inadequacies and weaknesses in the landscaping with a demand for living in a better environment and also with a comparison of the ideal or reference landscaping along with the intention to continue living in their current living place.…”
Section: Discussioncontrasting
confidence: 71%
“…As suggested by Stedman (2001, 2006), in this paper, under the umbrella term of "sense of place" covering cognitive, affective and behavioural domains of human-place relationships and the notions of place attachment, place identity and place dependence was preferred to use in order to investigate the people' relations with their living environment. As stated by Stokols and Shumaker (1981), Stedman (2002), Ramkissoon et al (2013) and Smith 2011, components of residents' sense of place, like "place identity", "place attachment" and "place dependence" are significantly associated with, and have positive influence on, feelings of satisfaction with the place. Place identity, which is a part of sense of place, refers to "dimensions of self that define the individual's personal identity in relation to the physical environment by means of a complex pattern of conscious and unconscious ideas, beliefs, preferences, feelings, values, goals and behavioural tendencies and skills relevant to that given environment" (Proshansky, 1978, p. 155).…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Lee et al, 2012;Ramkissoon et al, 2013;Veasna et al, 2013), place attachment has often been conceptualized as consisting of multiple subconstructs. The latter include place dependence (Stokols & Shumacker, 1981), place identity (Vaske & Kobrin, 2001;Walker & Chapman, 2003), place strike a balance between conservation and visitation, which remains invaluable to the sustainable future of resources in such settings.…”
Section: Place Attachmentmentioning
confidence: 99%
“…Studies examining place attachment provide good support for its multidimensional nature (e.g., Hidalgo & Hernandez, 2001;Scannell & Gifford, 2010a). However, little empirical work with the exception of a few (e.g., Ramkissoon et al, 2013aRamkissoon et al, , 2013bRamkissoon, Weiler, & Smith, 2013) have confirmed that place dependence, identity, affect, and social bonding together represent place attachment SATISFACTION AND PLACE ATTACHMENT IN NATIONAL PARKS 289 such expectations (Borrie & Birzell, 2001), aid planning, resource allocation, and service provision (Bushell & Griffin, 2006;Oh, 2001), and assist customization of experiences so that visitors obtain the natural and relaxation benefits they expect ( Crilley et al, 2012). For instance, Tonge and Moore's (2007) findings allowed expensive and politically unappealing proposals to be ruled out at the Swan Estuary Marine Park.…”
Section: Introductionmentioning
confidence: 99%